‘Quality of Life’ of Persons with Disability: An Assessment in Selected Flood Prone Areas of Bangladesh - Mahmud, Mir Hasan Shakil; Azad, Md. Abul Kalam (American International Journal of Social Science Research, 2017)
The present study is on “Quality of Life” of person with disabilities living in flood prone areas of Bangladesh. In this aspect the specific objectives have been designed to determine the effects of disaster on physical and psychological health and social relationship between disabilities and community. The study has also assessed the adaptive capacity of persons with disabilities during and post-disaster period and find out the challenges faced by the persons with disabilities during disaster and post disaster that undermining their quality of life. In the determination of quality of life of PWDs in the selected flood prone area in Bangladesh a mixed method incorporating both qualitative and quantitative research approaches was used to conduct this study by using the tools of observation, case study, and face to face semi structured interview, with PWDs in Northern district of Gaibandha. The study shows that out of 110 respondent, nearly 63 per cent required assistance, while over 38 per cent respondent are required partial assistance, and 20 percent are required supervision. The study reveals that more than 9 per cent of the respondents maintains very poor quality of life while 20 per cent are maintaining poor quality of life, nearly 34 per cent respondents are identified their life neither poor or nor good in selected area.